Influence of Students' Interests and Counseling Services on Subject Area Specialization Preferences Among Home Economics Students in Colleges of Education in Delta State - Abamba, Deborah Chibuzor; Arubayi D.O (Action Research Journal Indonesia (ARJI), 2024)
This study delves into the intricate relationship between students' interests, counseling services, and subject area specialization preferences among Home Economics students in Colleges of Education in Delta State. Employing a descriptive survey method and Pearson product-moment correlation research design, the study embraces a comprehensive approach to understand the intricate motivations driving students. The population under consideration comprises 381 Home Economics students across various Colleges of Education in Delta State, eliminating the need for sampling techniques due to the manageable size. The findings reveal that students' preferences within Home Economics are deeply rooted in intrinsic motivations, transcending traditional academic considerations. The study underscores the influential role of counseling services as catalysts in shaping academic and career trajectories. Well-equipped and accessible guidance and counseling units are identified as vital components, providing students with informed perspectives and unbiased opinions. The study offers practical implications for educational policies and practices. It advocates for flexible curricular structures that accommodate diverse preferences, emphasizing the need for continuous investment in counseling services.